Problem-based learning supported by digital archives: case study of Taiwan Libraries' History Digital Library. - Chen C (Electronic Library, 2010)
Purpose -- This paper seeks to assess the differences between learning performance and the satisfaction of learners who use digital resources in the Taiwan Libraries' History Digital Library (organized digital resources) and the Google search engine (unorganized digital resources) in problem-solving learning for the same subject via the problem-based learning (PBL) mode. The paper aims to explore the advantages and characteristics of using digital archives to support PBL and to offer suggestions that are helpful when using digital archives to support e-learning. Design/methodology/approach -- The study adopted the quasi-experimental design method to assign all participants into an experimental group and control group to evaluate differences in learning performance and the satisfaction of learners who use different digital resources during PBL processes. A statistical analysis scheme was employed to evaluate the learning performance of learners during PBL supported by different digital resources in terms of learning processes, PBL outcomes, and a questionnaire. Findings -- The study obtained the following conclusions: learning performance and the satisfaction of learners in the experimental group during PBL processes supported by digital archival resources were superior to those of control-group learners who were supported by search engine resources; compared with search engine resources, the digital archival resources provide benefits in the learning phase, such as 'action' (i.e. doing), in the proposed PBL mode, which has three learning phases; and compared with resources accessed through the Google search engine, PBL supported by digital archival resources should enhance searching performance and thereby increase learner willingness to use digital archives during e-learning. Practical implications -- Using digital archives to support e-learning is a new trend in the library sciences field; however, few studies have developed useful learning modes for effective e-learning supported by digital archives. Evidential research related to e-learning supported by digital archives is also lacking; most studies used digital archives as digital course materials, thus ignoring the principal property of digital archives -- excellent resource organization. Originality/value -- The paper shows that by integrating the PBL mode with digital archives one can identify the advantages of digital archives in supporting e-learning, resulting in innovative and valuable research.